In vitro and in vivo evaluation of quinones from Auxemma oncocalyx Taub. on Leishmania braziliensis - Viana, Sayonara de Melo (2015)
The effect of a quinone fraction (QF) isolated from the heartwood of Auxemma oncocalyx Taub. was investigated in vitro and in vivo on Leishmania braziliensis . Although QF (1-10 μ g/mL) showing marked in vitro anti- Leishmania activity (81 to 94%), the oral treatment with the compound did not protect hamsters against progressive L. braziliensis infection. When QF was administered intraperitoneally (20 mg/kg) the lesion size was reduced by 65%; however, it was not able to promote parasite eradication, as evidenced by the high number of parasites in dr aining lymph nodes. Quinones are highly redox active molecules and with their semiquinon es radicals can lead to formation of reactive oxygen species (ROS). The generation of ROS could probably explain the in vitro leishmanicidal activity of the quinones, since promastigotes are susceptible to H 2 O 2 lethal effect in vitro . In conclusion, although quinones seem to be effective against Leishmania parasites in vitro , they do not demonstrate a therapeutic effect in experimental leishmaniasis. In additi on, it can be hypothesized that QF in vivo might possibly be converted into non-active metabolite(s) or be inactivated either by reduction or by interaction with serum proteins, losing its leishmanicidal activity.